Group-theoretic vibration analysis of double-layer cable nets of D4h symmetry. (30th November 2019) - Zingoni, Alphose
Abstract: Shallow cable nets may be coupled into multi-layer configurations that are stiffer and stronger than single-layer configurations. In a previous study, group theory was used to investigate double-layer cable nets of D4h symmetry by reference to a 32-node case study, revealing key insights on their vibration characteristics. In this paper, and as an extension of the previous work, we present a rigorous group-theoretic formulation for the computation of natural frequencies and mode shapes of double-layer cable nets of D4h symmetry, by reference to the same case study. The analysis reveals the existence of transverse-extension modes that are unique to coupled cable-net configurations, at the same time demonstrating the substantial computational benefits of the group-theoretic procedure. A numerical example is considered in order to illustrate how the eigenvalues and eigenmodes of the problem are actually calculated, providing further insights on the vibration behaviour of the cable net.